Polymorphic variants of ABCA1, PMM2, and ARHGEF12 genes and the risk of glaucoma in an Iranian population - Asghar Shayannia; Kobra Foroughi; Mohammad Hassan Emamian; Hassan Hashemi; Akbar Fotouhi (International Journal of Ophthalmology)
AIM: To examine whether rs2472493 and rs248032 in the ABCA1 gene, rs3785176 in the PMM2 gene, and rs11827818 in the ARHGEF12 gene contribute to primary open angle glaucoma (POAG) in an Iranian population. METHODS: Totally 82 POAG patients and 172 healthy controls were enrolled. The selected gene polymorphisms were analyzed using TaqMan SNP Genotyping Assay using deoxyribonucleic acid (DNA) extracted from blood samples. Allelic and genotypic frequencies were evaluated using the Chi-square test. The association between the genotypes of single nucleotide polymorphisms (SNPs) and POAG was assessed using multiple logistic regression models. The linkage disequilibrium and haplotype block structure were assessed using the Haploview 4.2 software. RESULTS: The results showed a significant association between allele frequencies of rs2472493 in the ABCA1 gene locus and POAG [odds ratio (OR)=1.58, 95% confidence intervals (CI)=1.04-2.39, P=0.031]. The rs3785176 in the PMM2 gene was also associated with POAG in additive and over dominant genotypes. Moreover, haplotype analysis showed a significant association of two estimated haplotypes of rs2472493/rs2487032 with POAG. The AA haplotype showed a reduction in POAG risk (OR=0.41, 95%CI=0.202-0.834, P=0.012), while the GG haplotype was associated with the disease. In addition, this study could not discover any association between genotype and allele frequency of rs248032 in the ABCA1 gene, and rs11827818 in ARHGEF12 gene and POAG. CONCLUSION: rs2472493 in the ABCA1 gene can be considered a genetic susceptibility locus for POAG. The haplotype constructed with ABCA1 gene SNPs (rs2472493/rs2487032) is associated with POAG.